Combined Effects of Programmed Cell Death-1 Blockade and Endostar on Brain Metastases of Lung Cancer - Qi, Xuejiao; Zhao, Yinlong; Yang, Song; Sun, YuMeng; Liu, Honglei; Liu, Pengyu; Feng, Shiyao; Tui, Hongbo; Yuan, Zheng; Yang, Jiankai; Bu, Hui (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Background: The blockade of programmed cell death-1 (PD-1) and recombinant human endostatin can be used for the treatment of non-small cell lung cancer (NSCLC) and its metastasis. This study aims to explore the therapeutically potential of PD-1 blockade plus Endostar in brain metastasis of NSCLC. Methods: The mouse brain metastases model was established using Lewis lung carcinoma luciferase (LLC-Luc) and PC-9-Luc cells. Tumor metastasis in the brain and tumor burden were analyzed by using bioluminescence imaging (BLI), qRT-PCR and ELISA which were used to determine the mRNA and protein levels of biomarkers in tumor tissues. Immunohistochemical staining was used to determine the expression and location of CD31 in tumor tissues in the brain. Results: Treatment with anti-PD-1 and Endostar suppressed tumor metastasis in the brain and prolonged overall survival rate in LLC-Luc and PC-9-Luc brain metastases mouse model. In addition, treatment with anti-PD-1 and Endostar inhibited the expressions of CD31 and VEGF in tumor tissues in the brain. Furthermore, treatment with anti-PD- 1 and Endostar significantly suppressed the levels of IL1β, IFNγ, and TGFβ in the tumor tissues. Conclusion: The combination of PD-1 blockade and endostar suppressed brain metastases of NSCLC.
Keywords: brain metastasis